Efisiensi Alokasi Penggunaan Faktor Produksi pada Usahatani Padi di Kecamatan Wirosari Kabupaten Grobogan - Yuliana, Yuliana; Ekowati, T.; Handayani, M. (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
The purpose of this study was to analyze the influence factors of rice production and analyze economic efficiency of production factors usage of rice in the Wirosari District, Grobogan Regency. The research was conducted from October to November 2016 in Wirosari District. The method used in the study was survey method. To determine research location this study used purposive method while the respondent was chosen using simple random sampling with the number of respondents were 60 farmers. Data were analyzed by multiple linier regression with Cobb-Douglas function and calculation of economic efficiency. The result showed that the production factor affecting rice production was seed and NPK fertilizer. The usage of NPK fertilizer had not been economically efficient yet. Whilst the usage of seed was economically inefficient.Â